PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS KINERJA PEGAWAI - Rahmawati, Farida Dwi; Al-Habsyi, Achmad Zein Arsyad; Mardiyah, Mardiyah (MPI STAI Sangatta Kutai Timur, 2024)
The education system in Indonesia has problems, such as a low management system and work ethic, as well as inadequate quality and quantity of educators. Apart from that, in the field of education, intense competition, changes in the work environment, limited resources, and economic uncertainty are also challenges in developing human resources. So for this reason, it is necessary to develop human resources for our nation, both in companies and institutions. Thisresearch aims to find out and explore further human resource development in improving the effectiveness of the performance of teaching and education staff. In this article, we will discuss definitions, identification of needs, types, methods, and evaluation of existing problems. In this research, researchers used qualitative research and data collection techniques through literature studies, by writing studies from various references such as journals, books, or other things related to the theme raised, namely human resource development strategies in increasing effectiveness. Employee. Based on the results of the discussion that has been studied, researchers can conclude that, by investing time and resources to develop human resources, organizations can increase productivity and employee loyalty. High quality human resources will be better able to adapt to technological changes, overcome continually changing challenges, and be able to produce innovations.